Emotive Factor in Business English (on the material of English) - Smirnova, Elizabeth (My University, 2002)
The article describes emotive factor as an indicator of business speech behavior as well as its role in communicative tasks realization.
Keywords: emotive factor; speech behaviour; speech episode; емотивний фактор; мовленнєва поведінка; мовленнєвий епізод; эмотивный фактор; речевое поведение; речевой эпизод; кафедра іноземних мов професійного спрямування